Discovery and synthesis of the first selective BAG domain modulator of BAG3 as an attractive candidate for the development of a new class of chemotherapeutics. Issue 55 (21st June 2018) - Terracciano, Stefania; Lauro, Gianluigi; Russo, Alessandra; Vaccaro, Maria Carmela; Vassallo, Antonio; De Marco, Margot; Ranieri, Bianca; Rosati, Alessandra; Turco, Maria Caterina; Riccio, Raffaele; Bifulco, Giuseppe; Bruno, Ines
Abstract : The first selective BAG3BD modulator has been discovered. Abstract : BAG3 protein has emerged as a key regulator of important cellular processes and its expression is increased in some tumor types; however, despite its potential value for future chemotherapeutics, no selective BAG3 modulators have been yet reported. Here we report the 2, 4-thiazolidinedione derivative28 as the first BAG3 protein modulator.